A sustainability maturity model for micro, small and medium-sized enterprises (MSMEs) based on a data analytics evaluation approach. (15th August 2021) - Vásquez, Jenifer; Aguirre, Santiago; Puertas, Edwin; Bruno, Giulia; Priarone, Paolo C.; Settineri, Luca
Abstract: A maturity model for micro, small and medium enterprises (MSMEs) is introduced to assess the level of implementation of sustainability strategies and practices in this type of business. According to the literature, only a few sustainability-maturity assessment models intended for MSMEs have integrated the following three factors: environmental knowledge management, environmental strategies and good practices, and environmental management systems. The sustainability maturity model proposed here for MSMEs is capable of supporting the efforts of companies in their attempts to achieve both environmental sustainability and an improvement in their production systems. The model encompasses a four-level qualitative scale and uses supervised classification algorithms to categorize companies through data analysis techniques. After applying the model to a group of MSMEs from different productive sectors in Colombia, the results have shown that 6% of the companies were at an insufficient level, 31% were at an initial level, 45% at a developed sustainability maturity level, and 18% at a consolidated level. This result implies that the decision makers in the latter group have paid greater attention to the strengthening of sustainability progress capabilities and, hence, to the definition of a maturation route. Graphical abstract: Image 1 Highlights: A new sustainability maturity model for MSMEs is presented. The model has a four-level qualitative scale and uses data analysis techniques for classification. The model was applied to examine Colombian MSMEs in the different sectors. The results show that most of the companies are at the basic and development levels of sustainability.